2004
DOI: 10.1029/2003gc000614
|View full text |Cite
|
Sign up to set email alerts
|

Subduction Factory 3: An Excel worksheet and macro for calculating the densities, seismic wave speeds, and H2O contents of minerals and rocks at pressure and temperature

Abstract: [1] An Excel macro to calculate mineral and rock physical properties at elevated pressure and temperature is presented. The workbook includes an expandable database of physical parameters for 52 rock-forming minerals stable at high pressures and temperatures. For these minerals the elastic moduli, densities, seismic velocities, and H 2 O contents are calculated at any specified P and T conditions, using basic thermodynamic relationships and third-order finite strain theory. The mineral modes of suites of rocks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
308
2
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 278 publications
(321 citation statements)
references
References 47 publications
7
308
2
4
Order By: Relevance
“…Thermal variations alone cannot fully account for the observed high-velocity anomaly, which coincides with a low V P /V S ratio (Figure 7b). A temperature reduction of 400°C for a wide range of upper mantle compositions causes approximately a À0.5% change in V P /V S [Hacker and Abers, 2004;Boyd et al, 2004], much smaller than the observed anomaly (À1.5%). Resolution tests show that for features comparable to the interpreted, delaminated mantle lithosphere and the Indian mantle lithosphere beneath the eastern indentor, the inversion yields well-recovered V P /V S ratios, with magnitudes slightly less than those of the input anomalies (Figure 8).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Thermal variations alone cannot fully account for the observed high-velocity anomaly, which coincides with a low V P /V S ratio (Figure 7b). A temperature reduction of 400°C for a wide range of upper mantle compositions causes approximately a À0.5% change in V P /V S [Hacker and Abers, 2004;Boyd et al, 2004], much smaller than the observed anomaly (À1.5%). Resolution tests show that for features comparable to the interpreted, delaminated mantle lithosphere and the Indian mantle lithosphere beneath the eastern indentor, the inversion yields well-recovered V P /V S ratios, with magnitudes slightly less than those of the input anomalies (Figure 8).…”
Section: Resultsmentioning
confidence: 86%
“…Resolution tests show that for features comparable to the interpreted, delaminated mantle lithosphere and the Indian mantle lithosphere beneath the eastern indentor, the inversion yields well-recovered V P /V S ratios, with magnitudes slightly less than those of the input anomalies (Figure 8). So the magnitude of the real V P /V S ratio of the high-angle, high-velocity anomaly is likely greater than the observed value in Figure 7b, requiring a compositional change, which could be accounted for by a refractory mantle depleted of volatiles [Hacker and Abers, 2004;Boyd et al, 2004]. The fact that the high-velocity anomaly in the shallow mantle beneath the eastern indentor, which we identify as the Indian mantle lithosphere, also has a low V P /V S of a similar magnitude supports the interpretation that the high-dipping-angle, high-velocity anomaly is a sunken mantle lithosphere.…”
Section: Resultsmentioning
confidence: 99%
“…We have tried to fit the seismic velocities at temperatures indicated by the proposed geotherm and possible mantle peridotite compositions, using the spreadsheet proposed by Hacker and Abers (2004). However, the reasonable fit for V s was obtained only for the uppermost mantle (down to ca.…”
Section: Discussionmentioning
confidence: 99%
“…9 Summary of composition modeling. Diagrams show density, V p velocity, V s velocity, and an example of lithospheric mantle compositions used for model calculation by Hacker and Abers (2004) spreadsheet. The primitive mantle after Johnson et al (1990) assumed to contain no melt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation